2020
DOI: 10.1101/2020.04.06.20055475
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human monoclonal antibodies block the binding of SARS-CoV-2 spike protein to angiotensin converting enzyme 2 receptor

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused a global pandemic of novel corona virus disease (COVID-19). To date, no prophylactic vaccines or approved therapeutic agents are available for preventing and treating this highly transmittable disease. Here we report two monoclonal antibodies (mAbs) cloned from memory B cells of patients recently recovered from COVID-19, and both mAbs specifically bind to the spike (S) protein of SARS-CoV-2, block the binding of receptor binding domain… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 20 publications
0
31
0
1
Order By: Relevance
“…Due to the critical role of the CoV spike (S) protein in viral entry, Abs targeting S, particularly in the receptor binding domain (RBD), have demonstrated their ability to neutralize the infectivity of CoVs (1-5) including SARS-CoV-2 (6)(7)(8). Studies of monoclonal Abs isolated from SARS-CoV-2-infected individuals have shown potent anti-viral effects in vitro and protected against viral challenge in mouse, hamster, and nonhuman primate models (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), motivating monoclonal antibody-based therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the critical role of the CoV spike (S) protein in viral entry, Abs targeting S, particularly in the receptor binding domain (RBD), have demonstrated their ability to neutralize the infectivity of CoVs (1-5) including SARS-CoV-2 (6)(7)(8). Studies of monoclonal Abs isolated from SARS-CoV-2-infected individuals have shown potent anti-viral effects in vitro and protected against viral challenge in mouse, hamster, and nonhuman primate models (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), motivating monoclonal antibody-based therapies.…”
Section: Introductionmentioning
confidence: 99%
“…The detection of circulating antibodies against SARS-CoV-2 may inform on immunity to the virus, and ongoing efforts toward sensitive and specific assays include the development of lateral flow chromatographic immunoassay or ELISA. The receptor binding domain of spike protein (S-RBD) emerged as a potential antigen against which humoral immunity may develop, and the role of S-RBD in viral entry suggests antibodies against these proteins may present with neutralizing properties and immunity to COVID-19; recent studies have suggested such a possibility (10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the critical role of the spike (S) protein in viral entry, Abs targeting S, particularly in the receptor binding domain (RBD), have been shown to neutralize the infectivity of CoVs (Chan et al, 2009;Sui et al, 2004;ter Meulen et al, 2006;Traggiai et al, 2004;Zhu et al, 2007) including SARS-CoV-2 (Chen et al, 2020;Wang et al, 2020;Ye et al, 2020). Studies of monoclonal Abs isolated from SARS-CoV-2infected individuals have shown potent anti-viral effects in vitro and protection from viral challenge in mouse and nonhuman primate models (Cao et al, 2020;Hassan et al, 2020;Imai et al, 2020;Ju et al, 2020;Pinto et al, 2020;Rogers et al, 2020;Salazar et al, 2020;Shi et al, 2020;Wec et al, 2020;Yuan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%